Optimizing the Expansion and Engineering of X-XP Express’s Logistics Facilities in West Java to Handle Surge in Shipping Volume During the “Twin Dates” and “Pay Day Sale” Periods - Elfa Firdy Gunawan; Nur Aisyah; Harkaffi Wilmar; Estu Hafiz Pamungkas (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid growth of e-commerce has intensified operational challenges for logistics providers, particularly during double-date promotional campaigns and Pay Day Sale periods that generate substantial surges in shipment volume within a limited timeframe. This study investigates the operational performance of X-XP Express logistics facilities in West Java and evaluates strategies for optimizing facility capacity and workforce allocation under peak-demand conditions. An empirical quantitative case-study approach was employed using operational records, shipment-volume data, facility-capacity information, and manpower allocation data collected from Distribution Center operations in the Bandung–Cimahi region. The analytical framework integrates a Multi Channel–Single Phase (M/M/s) queueing model, logistics-network simulation using AnyLogistix, and discrete-event simulation using AnyLogic. The results indicate that the initial system operated at a utilization level of 0.94, with an average queue length of 10.95 packages and a waiting time of 26.28 seconds. Capacity expansion and manpower adjustments reduced utilization to 0.77, decreased queue length to 0.40 packages, and shortened waiting time to 0.24 seconds. Network simulation further demonstrated that a three-Distribution-Center configuration achieved full demand coverage within the modeled service radius. The study highlights the effectiveness of simulation-based logistics engineering in improving operational resilience, service performance, and capacity management during periods of extraordinary demand.